A constituição de mulher no seriado The Good Wife - dialogia no seriado e na fanfic - Gomes, Ana Luzia Chavez (2016)
This research presents an analysis about the woman’s constitution in television series, specifically the series The Good Wife in dialogue with fanfiction, which are textual productions of the fans. The approach taken is the bakhtinian one in the sense that the worlds constructs are social and television is a very influential mechanism in society. Thus, issues such as dialogy, speech genres and constitution of the subject are treated, allowing the construction of a theoretical background. Think about women’s presence in society is interesting, since we are in a period in which women are increasingly inserted breaking old paradigms. But it’s also necessary to note that even with the changes, it still has a mindset that sometimes limits such insertion, so be aware enables break with these limitations.